Facilitators and barriers in the implementation of patient-centred care interventions among general practitioners: a systematic review protocol - Wenhui Li; Min Su; Zhengrong Li; Xiaojing Fan (Health Research Policy and Systems)
Abstract Background Challenges in the patient–provider relationship are prevalent, underscoring the importance of patient-centred care, which is respectful and responsive to patients’ needs. General practitioners (GPs), also known as family doctors, serve as gatekeepers in primary care and are well positioned to deliver this type of care. However, effectively implementing patient-centred care remains a challenge. While behaviour change interventions have been developed to enhance patient-centred care in general practices, a comprehensive understanding of the facilitators and barriers to their implementation is lacking. This review aims to examine contextual factors of implementing interventions for patient-centred care by GPs. Implementation research analyses all aspects of application, including factors influencing it, processes involved and outcomes achieved within different contexts. The review will use the updated Consolidated Framework for Implementation Research (CFIR 2.0) to analyse influential factors and the Behaviour Change Wheel (BCW) to define interventions to promote behaviour change in patient-centred care. Methods This systematic literature review will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of five databases (Ovid MEDLINE, CINAHL, EMBASE, Cochrane Library and Web of Science) will be conducted to identify barriers and facilitators for implementing interventions in promoting patient-centred care by GPs. The CFIR 2.0 framework will guide the categorization and synthesis of barriers and facilitators, while the BCW will be employed to define the interventions. Two independent reviewers will conduct study screening, data extraction, quality appraisal and data analysis. Any disagreements between the reviewers will be resolved through the involvement of additional reviewers. Discussion This protocol outlines a systematic review utilizing an updated framework-based approach to identify and synthesize evidence on barriers and facilitators to implementing behaviour change interventions by GPs. The findings will provide insights into the effectiveness of these interventions in enhancing patient-centred care and will inform future research and clinical practice. This review will identify gaps and challenges in existing studies and propose strategies for the effective implementation of behavior change interventions among GPs. Additionally, it will inform clinical practice by refining behaviour change interventions to enhance the delivery of patient-centred care by GPs. Trial registration: PROSPERO: CRD42023485014.